Kewenangan Komisi Penyiaran Indonesia Daerah (KPID) Sulawesi Tengah Terhadap Kode Etik Penyiaran Pada Lembaga Penyiaran Radio - Widyatmi Anandy; Irzha Friskanov. S (Faculty of Law, Universitas Riau, 2022)
The Indonesian Broadcasting Commission (KPI) is an independent institution in Indonesia whose position is at the same level as other state institutions that function as a regulator of broadcasting in Indonesia. The KPI consists of the Central Indonesian Broadcasting Commission (KPI) and the Regional Indonesian Broadcasting Commission (KPID) that work at the provincial level. The authority and scope of duties of the Broadcasting Commission covers broadcasting arrangements organized by Public Broadcasting Institutions, Private Broadcasting Institutions, Subscriber Broadcasting Institutions and Community Broadcasting Institutions. Radio is a media facility that still exists in Palu City. Radio media is a place for audio connoisseurs to accompany work and even travel. It is undeniable that radio is a powerful means of providing information. With a distinctive way of presentation, radio is still the main attraction. Radio listeners are served small talk and accompanied by songs. In this regard, radio broadcasters do not escape the status of a profession that is bound by a code of ethics. The Regional Indonesian Broadcasting Commission (KPID) of Central Sulawesi is an independent state institution that is responsible for controlling broadcasting behavior in each broadcasting institution, including radio. This problem is the background for the author to discuss it in research, first, how is the authority of the Central Sulawesi KPID towards the broadcasting code of ethics in radio broadcasting institutions. Second, how is the standard of behavior of radio broadcasting institutions in Palu. Duties and responsibilities, the authorities possessed by the Regional Indonesian Broadcasting Commission (KPID) of Central Sulawesi have indirect responsibilities with the State.